Design and development of an algorithm for mining rare item sets - Sachin Sharma; Shaveta Bhatia (Institute of Advanced Engineering and Science, 2019)
Frequent item set mining emphases on excavating item sets which follow frequently in a transactional database. These item sets are advantageous in professional decision making. Investigators have projected numerous processes to mine rare item sets, however it is still stimulating. In current studies, to catch rare item sets, customer demarcated single threshold value ought be fixed small adequate which outcomes in generation of enormous quantity of duplicate item sets. The rare item sets may not initiate if a high threshold value is fixed. In this study, an exertion is generated to analyse the rare items for discovery of all probable rare item sets from the transaction database. To mine rare item sets effectually, a method has been anticipated that would permit customer to identify many lowest support that imitates the items and their diverse occurrences in list. Investigational results shows that novel methodology is more righteous and vigorous than the present systems.